GOLD INVESTMENT PATTERN ANALYSIS DURING THE PANDEMIC: AN OVERHAUL - Vikram, Mrs. Prathibha; Kumar Sinha, Dr. Rajendra (The journal of contemporary issues in business and government, 2022)
The perception of Gold in an Indian Investor is different from that of a foreign investor. If there is any one investment that runs through all throughout the year for an Indian, it is definitely gold. This paper examines the pattern of Gold investment during the pandemic - Covid 19 by individual investors. The paper is based on the primary data analyzed through the questionnaire prepared for the purpose of studying the shift in priorities of individual Investors during the pandemic and with the new normal. This paper highlights the brighter side of investing in gold at different periods with different income groups is observed. It examines the relative performance of the gold investment in the portfolio carried by the investor during the lockdown period. The factors affecting the investment of every individual with varied income is analyzed and tested with descriptive Statistics. The study proceeds to acquire the resultant estimation of whether there is a significant change in the investment of Gold or has gold sustained the wave of this economic crisis during the Covid period.